Paleolithic diet during pregnancy—A potential beneficial effect on metabolic indices and birth weight. (November 2019) - Lavie, Michael; Lavie, Inbar; Maslovitz, Sharon
Abstract: Background: Paleolithic diet has recently gained popularity due to its presumed health benefits. The favorable metabolic effects of this diet were assessed in non-pregnant population but its impact during pregnancy remains to be evaluated. Study design: A retrospective cohort study comparing two groups. Group A comprised of women with singleton low-risk pregnancy adherent to paleolithic diet throughout gestation (n = 37). Group B comprised low risk pregnant women on a regular diet (n = 39). Women were excluded if they had low adherence to diet, started paleolithic diet during pregnancy, and had pre-gestational diabetes mellitus or other types of metabolic syndrome such as pre gestational hyperlipidemia, hypertension or BMI > 35. Blood indices such as Glucose challenge test scores, hemoglobin, ferritin, and TSH levels were compared. Other pregnancy factors such as maternal weight gain, rest days during gestation and pregnancy complications such as IUGR, GDM or preeclampsia were compared. Lastly, obstetrical outcomes such as mode of delivery and complications such as high-grade tears, as well as neonatal factors such as birth weight and pH were compared between the two groups. Results: General maternal characteristics such as age, BMI and parity were comparable between the two groups. Women who maintained a paleolithic diet had a significant decrease in glucose challenge test scores (95.8 mg/dL vs. 123.1 mg/dL, p < 0.01) and increase in hemoglobin levels (12.1 g/dL vs. 11.05 g/dL p < 0.01) and Ferritin (32.1 vs 21.3 mg/mL, p = 0.03) compared to women maintaining regular diet. Maternal pregnancy weight gain was also slightly decreased in group A (9.3Kg vs. 10.8 kg, p = 0.03). Birthweights were lower in group A (3098 g Vs.3275 g, p = 0.046) with no difference in adverse neonatal outcomes. We found no differences in other pregnancy complications or labor outcomes such as mode of delivery, shoulder dystocia or high grade perineal tears. Conclusion: Paleolithic diet maintained during pregnancy may have a beneficial effect on the glucose tolerance. It also may increase iron stores and hemoglobin levels. Neonates of women maintaining paleolithic diet are slightly lighter but appropriate for gestational age with no difference in neonatal outcomes.